2016
DOI: 10.1002/2016ja023161
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of SABER CO2‐based eddy diffusion coefficients in the lower thermosphere on the ionosphere/thermosphere

Abstract: This work estimates global‐mean Kzz using Sounding of the Atmosphere using Broadband Emission Radiometry/Thermosphere‐Ionosphere‐Mesosphere Energetics and Dynamics monthly global‐mean CO2 profiles and a one‐dimensional transport model. It is then specified as a lower boundary into the Thermosphere‐Ionosphere‐Electrodynamics General Circulation Model (TIE‐GCM). Results first show that global‐mean CO2 in the mesosphere and lower thermosphere region has annual and semiannual oscillations (AO and SAO) with maxima … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(64 citation statements)
references
References 67 publications
(140 reference statements)
7
57
0
Order By: Relevance
“…The standard TIME‐GCM simulation also agrees well with observations, demonstrating that this model is capable of producing a realistic global T‐I SAO from first principles. The globally averaged K z z in Figure c from the standard TIME‐GCM simulation shows a much smaller SAO than the Qian et al [] K z z variation but is consistent with the small K z z variation derived by Salinas et al [] from SABER CO 2 observations. Without gravity waves TIME‐GCM still produces a reasonable T‐I SAO, which strongly suggests that seasonally varying K z z driven by breaking gravity waves (the K z z hypothesis) is not the primary driver of this phenomenon.…”
Section: Model Results and Comparisons With Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard TIME‐GCM simulation also agrees well with observations, demonstrating that this model is capable of producing a realistic global T‐I SAO from first principles. The globally averaged K z z in Figure c from the standard TIME‐GCM simulation shows a much smaller SAO than the Qian et al [] K z z variation but is consistent with the small K z z variation derived by Salinas et al [] from SABER CO 2 observations. Without gravity waves TIME‐GCM still produces a reasonable T‐I SAO, which strongly suggests that seasonally varying K z z driven by breaking gravity waves (the K z z hypothesis) is not the primary driver of this phenomenon.…”
Section: Model Results and Comparisons With Observationsmentioning
confidence: 99%
“…IAVs in (a) globally averaged mass density at 400 km and (b) TEC in % relative to their global and annual averages. (c) Globally averaged normalized K z z from the NCAR TGCMs and Salinas et al [] as a function of day of year at the TIE‐GCM lower boundary of 5.483 × 10 −4 mbar (∼97 km) and at 98 km, respectively. Shown are TIME‐GCM simulations that include both gravity waves and GSWM‐09 tides (“Standard,” black‐plus signs), only GSMW‐09 tides (orange asterisks), and neither gravity waves nor GSWM‐09 tides (purple triangles); TIE‐GCM results with the Qian et al [] seasonally varying K z z (blue squares); empirical mass density and TEC models (red Xs) developed by Emmert [] and Emmert et al []; and Salinas et al [] SABER CO 2 ‐based K z z at 98 km (green diamonds).…”
Section: Model Results and Comparisons With Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Calabia et al (2016) investigated the thermospheric mass density variations from GRACE data for the period 2003-2016 by using the principal component analysis (PCA) method, and discussed the annual variation for different local solar times (LSTs) and solar activities. Moreover, Salinas et al (2016) found that the monthly global-mean CO 2 profiles from TIMED/SABER have annual and semiannual oscillations (AO and SAO), but cannot explain the observed AO and SAO in the thermosphere. However, Jones et al (2017) reported that simulations from the Thermosphere Ionosphere Mesosphere Electrodynamics General Circulation Model (TIMEGCM) demonstrated that the intra-annually varying eddy diffusion by the breaking gravity waves may not be the primary driver of the SAO in the thermosphere.…”
Section: Introductionmentioning
confidence: 92%
“…Then, they reduced the constant K zz by a factor of 5 and obtained a larger SAO in the ionosphere, which is comparable to the standard GSWM (global scale wave model) run of TIEGCM with a standard constant K zz . Salinas et al () used K zz based on SABER CO 2 observation ( K zzC ) to drive the TIEGCM; the K zzC is smaller than that from Q09 with a smaller SAO. Their TIEGCM simulation with K zzC produced smaller SAO in the ionosphere compared to the observations and Q09.…”
Section: Introductionmentioning
confidence: 99%